Studi Deskriptif Sekolah Ramah Anak di Taman Kanak-Kanak Pertiwi 1 Kantor Gubernur Padang - Rahmi, Nicky Zonita; Marlina, Serli (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to evaluate the implementation of child-friendly education at Pertiwi 1 Kindergarten at the Governor's Office. The methods used are observation and interviews with teachers as well as analysis of school documents. The research results show that Pertiwi 1 Kindergarten has implemented seven child-friendly school policy indicators, including anti-violence and anti-discrimination policies, as well as written SOPs for follow-up to violence. This school also meets six of the seven indicators for curriculum implementation, such as providing RPPM and RPPH, arranging classrooms, and providing play equipment and wall decorations. However, a curriculum based on children's rights is not yet available. In addition, five teachers at this school claim to understand children's rights and child-friendly education, with four of the five teachers having PAUD degrees and having attended related training. Another teacher has more than 10 years of work experience and has also attended several seminars. The conclusion of this research is that Pertiwi 1 Kindergarten has succeeded in implementing most of the indicators of child-friendly education, but still needs to improve aspects of the children's rights-based curriculum to achieve the desired standards.